Managing gout in primary care - Perez-Ruiz, Fernando (Springer Healthcare Ltd., 2014)
This handbook discusses developments and the future of gout treatment, which looks promising. Gout has been a well-known disease for over 2000 years, and is the most common cause of joint inflammation in adult males. It has become apparent that no therapeutic target based on hyperuricemia outcome had been defined. Very few controlled trials were available to test the efficacy and safety of treatments, and no research on diagnosis and management had been done despite data showing that patients with gout were generally improperly treated even in the hands of specialists. In the last 10 years, good-quality evidence on gout impact and management has grown exponentially, renal transporters have been recently identified, and a number of new drugs have been approved or are under current development.